Analisis Ragam Desain Fasilitas Duduk pada Interior Area Baca DISPUSIPDA Jawa Barat - Elfreda, Felicia Athalia; Santoso, Miky Endro; Sugiharto, Nathalia Yunita (Program Studi Desain Interior Unikom, 2021)
For some students, the library was chosen because it has various types of reading and the many facilities provided, one of which is sitting facilities. When reading, sitting position affects the comfort in reading. Therefore, the variety of seating facilities provided is important to know the various designs of the seating facilities to suit student preferences, especially in the public library which is a place to read or do assignments. This study uses a quantitative method with an exploratory approach by collecting data from the literature review and comparing the data from the questionnaire to draw conclusions. Physical comfort is the main thing that needs to be in every sitting facility by paying attention to the impact of its use on body posture or back area, especially when the sitting facility will be used for a long time. Bean bags and conventional chairs are the most widely chosen because of their comfort and good in preventing back and neck pain and maintaining a comfortable body position. The selection of types and types of seating facilities affects the comfort of visitors for each type of activity.